Consensus statement on the management of breakthrough cancer pain: Assessment, treatment and monitoring recommendations - María Dolores López Alarcón; Francisco Villegas Estevez; Vicente Domingo Triado; Pilar Blasco Segura; Genoveva Hernández Comes; Alfonso Berrocal Jaime; Ana Blasco Cordellat; Jorge Pastor Peidro; José López Torrecilla; Carlos Ferrer Albiach; Almudena Ruiz Sastre; Manuel Hernández Peris (Open Journal of Pain Medicine - Peertechz Publications, 2019)
Objective: Breakthrough cancer pain (BTcP) is still underestimated and a percentage of patients are not adequately treated, affecting their quality of life. The aim of this review was to generate a series of expert recommendations based on clinical experience and current scientifi c data on the management of BTcP. Methods: An interdisciplinary group of Spanish pain experts held face-to-face meetings to review existing protocols and the relevant scientifi c literature on the management of BTcP, sharing their clinical experience. The outcome was a consensus document, providing practical guidelines and suggestions on the diagnosis, treatment and follow-up of BTcP patients.